2017
DOI: 10.3389/fpls.2017.00477
|View full text |Cite
|
Sign up to set email alerts
|

SVP-like MADS Box Genes Control Dormancy and Budbreak in Apple

Abstract: The annual growth cycle of trees is the result of seasonal cues. The onset of winter triggers an endodormant state preventing bud growth and, once a chilling requirement is satisfied, these buds enter an ecodormant state and resume growing. MADS-box genes with similarity to Arabidopsis SHORT VEGETATIVE PHASE (SVP) [the SVP-like and DORMANCY ASSOCIATED MADS-BOX (DAM) genes] have been implicated in regulating flowering and growth-dormancy cycles in perennials. Here, we identified and characterized three DAM-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
144
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(150 citation statements)
references
References 45 publications
6
144
0
Order By: Relevance
“…For instance, flowering and growth cessation in poplar are regulated by a CO/FT regulatory module (Böhlenius et al ., ), and induction of poplar bud dormancy requires the transcriptional regulation by ABA of an ortholog of SHORT VEGETATIVE PHASE (SVP; Singh et al ., ). Orthologs of SVP have been implicated in seasonal control of growth arrest in apple and kiwifruit (Wu et al ., , ). Multiple FT homologs, as well as FLD, LFY and AP1 homologs, have been identified and associated with bud dormancy in several temperate tree species (Cooke et al ., ; Lloret et al ., ).…”
Section: Examples Of Genetic Pleiotropy Of Flowering‐time Genes In Amentioning
confidence: 99%
“…For instance, flowering and growth cessation in poplar are regulated by a CO/FT regulatory module (Böhlenius et al ., ), and induction of poplar bud dormancy requires the transcriptional regulation by ABA of an ortholog of SHORT VEGETATIVE PHASE (SVP; Singh et al ., ). Orthologs of SVP have been implicated in seasonal control of growth arrest in apple and kiwifruit (Wu et al ., , ). Multiple FT homologs, as well as FLD, LFY and AP1 homologs, have been identified and associated with bud dormancy in several temperate tree species (Cooke et al ., ; Lloret et al ., ).…”
Section: Examples Of Genetic Pleiotropy Of Flowering‐time Genes In Amentioning
confidence: 99%
“…Furthermore, plants overexpressing QsSVP4 had flowers with extra petals and sepals. The late flowering and the flower organ number phenotypes derived from overexpressing QsSVP4 were previously described in other studies in which SVP -like genes of several perennial species were overexpressed in perennial and annual species (Li et al 2010, Wu et al 2012, 2017, Jaudal et al 2014). In Q. suber , both QsSVP1 and QsSVP4 are highly expressed during early stages of axillary bud growth cessation, suggesting a conserved role for these genes in growth arrest.…”
Section: Discussionmentioning
confidence: 64%
“…In perennial species of temperate climates, a subset of meristems needs to remain vegetative to sustain consecutive growth cycles that are interrupted by unfavourable environmental conditions. Axillary bud growth cessation and bud swelling in perennials, like kiwifruit and peach, is controlled by the regulation of the transcription machinery, particularly by SVP -like genes that respond to environmental cues (Li et al 2009, Wu et al 2012, 2017). Of the four QsSVP genes, only QsSVP1 and QsSVP4 were able to delay flowering in transgenic Arabidopsis plants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that the openness of flower buds in woody plants was related to dormancy release [13][14][15]. Before the spring flowering of 'Changchun', the long dormancy process of flower buds was released, and the growth amount increased significantly.…”
Section: Flowering Initiation Is An Important Stage During 'Changchunmentioning
confidence: 95%
“…However, to date, the understanding of flowering regulation in woody plants has been based on the molecular mechanisms underlying the regulation of flower bud differentiation.In fact, for temperate perennial woody plants with multiple flowering, the buds formed by reproductive transition can flower after a period of dormancy [11,12]. Taking apical buds and flowers from Malus × domestica 'Royal Gala' as materials, researchers found that MdDAMb (DORMANCY ASSOCIATED MADS-BOX), MdSVPa, and MdSVPb played a role in maintaining bud dormancy, and SVP (SHORT VEGETATIVE PHASE) might play a role in floral meristem identity [13]. The increased level of PpEBB (EARLY BUD-BREAK) induced high levels of transcription of four PpCYCD3 (D-type CYCLIN) genes, which promoted cell division and resulted in a significant increase in the primordia size of Pyrus pyrifolia 'Kosui' lateral flower buds [14].…”
mentioning
confidence: 99%